7th Eurasian Conference “RİSK-2025” and Newly Created Journal “International Journal of Sustainability and Risk Control” - Aliyev, V. (Journals of Georgian Geophysical Society, 2025)
Information by Prof. V. Aliyev about the 7th Eurasian Conference “RİSK-2025” to be held on October 21-23, 2025 in Baku (Azerbaijan), as well as the newly created journal “International Journal of Sustainability and Risk Control” and its first issue which was published at the end of June 2025, is presented.